Effects of Areca Catechu L. Seed Extract on Mortality Anopheles Vagus Larvae (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Bioinsecticide is an alternative to overcome larva resistence to insecticide and reduce environtment contamination. This research is to analyze the effect of areca seed extract to An. vagus larva. The research is taken time in 2017. The research design is laboratory experiment with post test only control group design. The areca seed and An. vagus larva are collected from Kabupaten Sumba Barat Daya, then the seeds were extracted with ultrasonic method. The effect of the extract is evaluated based on LC50 and LC90 value. The sample from 25 An. vagus larva instar III are released into areca seed extract on 500, 1250, 2000, 2750, 3500, 4250 and 5000 ppm and observed within 6, 12, 18 and 24 hours and 6 repetition. The data then analyzed with probit analysis and ANOVA. The areca seed extract eliminates An. vagus larva as much as 61.33% under 6 hours exposure with 5000 ppm, 52% larva mortality on 12 hours with 4250 ppm, 56% larva mortality on 18 hours with 3500 ppm, and 55% larva mortality on 24 hours with 2750 ppm. The value of LC50 and LC90 on 6, 12, 18 and 24 hours are 4654.374 and 6320,732; 3717.286 and 5127.489 ppm; 3201,473 and 4775,206 ppm; 2385,297 and 4496,708 ppm. There is variation of larva mortality percentage average on every concentration and exposure time, the higher the concentration and exposure time the higher An. vagus larva mortality.